(untitled) (gjstudies, 2018)
This research investigates the complex and often paradoxical relationship betweencorporate tax planning strategies and long-term financial performance, moving beyond conventional efficiency metrics to propose a novel, multi-dimensional performanceframework. While traditional literature predominantly frames tax planning as a valueenhancing activity through cash flow preservation, this study posits that aggressivetax strategies can generate significant hidden costs and risks that erode sustainablecompetitive advantage. We introduce the concept of ’Tax-Induced Strategic Myopia,’a phenomenon where excessive focus on tax minimization distorts capital allocation,incentivizes suboptimal operational decisions, and weakens organizational resilience.Through a mixed-methods approach combining a longitudinal analysis of financialdata from SP 500 firms (2010-2023) with qualitative case studies derived from executive interviews and internal audit reports, we develop a tripartite model linking taxstrategy to performance via three mediating channels: reputational capital, innovationcapacity, and strategic flexibility. Our results reveal a non-linear, inverted U-shapedrelationship, where moderate tax planning enhances performance, but beyond an optimal threshold, incremental tax savings correlate negatively with long-term profitability,market valuation, and innovation output. The findings challenge the prevailing ’lowereffective tax rate equals superior performance’ axiom and contribute a new theoreticallens for evaluating corporate tax strategy as an integral component of strategic riskmanagement rather than a purely financial engineering exercise.